Religion and Power in Hobbes and Marsilius of Padua: Similarities and Differences - Aznar, Bernardo Bayona (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
Marsilius of Padua developed a political theory very different from traditional medieval thought and he made an unprecedented attempt to base power on rational grounds. The Anglican Reform used a great deal of ideas taken from Marsilius’ Defensor pacis, a work that has often been seen as an original anticipation of the modern theory of State. This article presents an investigation into the close and striking similarities between Marsilius and Hobbes on the status of religion and papal power. Both authors were strongly touched by the civil war, which they attributed to the temporary power of the Pope. Therefore they defended the exclusion of the Roman Church from all power in this world, in order to remove coexisting and competing governments and jurisdictions, as a condition for maintaining peace. Even though the number of similar arguments in Marsilius’ and Hobbes’ theories show a great continuity between their political discourses, this essay also analyses the notorious differences between their thoughts, built in different times and with very different philosophical elements.